Effect of chloroquine on gene expression of Plasmodium yoelii nigeriensis during its sporogonic development in the mosquito vector - Silveira, Henrique (2021)
Background. The anti-malarial chloroquine can modulate the outcome of infection during the Plasmodium sporogonic development, interfering with Plasmodium gene expression and subsequently, with transmission. The present study sets to identify Plasmodium genes that might be regulated by chloroquine in the mosquito vector. Methods. Differential display RT-PCR (DDRT-PCR) was used to identify genes expressed during the sporogonic cycle that are regulated by exposure to chloroquine. Anopheles stephensi mosquitoes were fed on Plasmodium yoelii nigeriensis-infected mice. Three days post-infection, mosquitoes were fed a non-infectious blood meal from mice treated orally with 50 mg/kg chloroquine. Two differentially expressed Plasmodium transcripts (Pyn_chl091 and Pyn_chl055) were further characterized by DNA sequencing and real-time PCR analysis. Results. Both transcripts were represented in Plasmodium EST databases, but displayed no homology with any known genes. Pyn_chl091 was upregulated by day 18 post infection when the mosquito had a second blood meal. However, when the effect of chloroquine on that transcript was investigated during the erythrocytic cycle, no significant differences were observed. Although slightly upregulated by chloroquine exposure the expression of Pyn_chl055 was more affected by development, increasing towards the end of the sporogonic cycle. Transcript abundance of Pyn_chl055 was reduced when erythrocytic stages were treated with chloroquine. Conclusion. Chloroquine increased parasite load in mosquito salivary glands and interferes with the expression of at least two Plasmodium genes. The transcripts identified contain putative signal peptides and transmembrane domains suggesting that these proteins, due to their location, are targets of chloroquine (not as an antimalarial) probably through cell trafficking and recycling.